X0(2900) and its heavy quark spin partners in molecular picture *This work is partly supported by the National Natural Science Foundation of China (NSFC) and the Deutsche Forschungsgemeinschaft (DFG) through the funds provided to the Sino-German Collaborative Research Center "Symmetries and the Emergence of Structure in QCD" (NSFC Grant No. 12070131001 and DFG Grant No. TRR110), Science and Technology Program of Guangzhou (2019050001), NSFC Grant No. 12035007, Guangdong Provincial funding with (2019QN01X172). MWH and XYL are also supported by Entrepreneurship competition for College Students of SCNU. (February 2021) - Hu 胡, Mei-Wei 美薇; Lao 劳, Xue-Yi 雪怡; Ling 凌, Pan 攀; Wang 王, Qian 倩
Abstract: The, recently observed by the LHCb Collaboration in the invariant mass of the process, is the first exotic candidate with four different flavors, beginning a new era for the hadron community. Under the assumption that the is a hadronic molecule, we extracted the whole heavy-quark symmetry multiplet formed by the doublet and the meson. For the bound state case, there would be two additional hadronic molecules associated with the and channels, as well as one additional molecule. In the light quark limit, they are and below the and thresholds, respectively, which are unambiguously fixed by the mass position of the . For the virtual state case, there would be one additional hadronic molecule, strongly coupled to the channel, and one additional molecule. Searching for these heavy quark spin partners will help shed light on the nature of the .